Oral and Intramuscular Treatment Options for Early Postpartum Endometritis in Low-Resource Settings: A Systematic Review. Issue 4 (April 2015) - Meaney-Delman, Dana; Bartlett, Linda A.; Gravett, Michael G.; Jamieson, Denise J.
Abstract : OBJECTIVE: To suggest options for oral and intramuscular antibiotic treatment of early postpartum endometritis in low-resource community settings where intravenous antibiotics are unavailable. DATA SOURCES: Studies were identified through MEDLINE from inception through December 2014. Search terms included [("anti-bacterial agents [MeSH]" or "anti-infective agents [MeSH]") and ("endometritis [MeSH]" or "puerperal infection [MeSH]")]. A second search using the terms [("endometritis or endomyometritis or puerperal infection) and ("antibiotics or antimicrobials or anti-bacterial agents or anti-infective agents)"] was also used. Additionally, all references from selected articles were reviewed, a hand-search of a subject matter expert library was conducted, and a search of ClinicalTrials.gov was performed. METHODS OF STUDY SELECTION: We conducted a systematic review of the literature in two phases. Phase I provides a summary of clinical cure data from prospective studies of oral and intramuscular antimicrobial regimens as well as summarizes evidence from trials of intravenous antimicrobials. Phase II is a quantitative analysis of pathogens from intrauterine postpartum endometritis samples. Based on these results, and with consideration of existing recommendations for antibiotic use during breastfeeding, we suggest oral and intramuscular antimicrobial options for the treatment of early postpartum endometritis after vaginal delivery in low-resource settings. TABULATION, INTEGRATION, AND RESULTS: Reports involving oral or intramuscular antimicrobial treatment of postpartum endometritis are rare and of generally poor quality. Antimicrobial trials of postpartum endometritis treatment and intrauterine microbiology studies suggest five antimicrobial regimens may be effective: oral clindamycin plus intramuscular gentamicin, oral amoxicillin–clavulanate, intramuscular cefotetan, intramuscular meropenem or imipenem–cilastatin, and oral amoxicillin in combination with oral metronidazole. CONCLUSION: This review provides suggestions for oral, intramuscular, and combined antimicrobial regimens that may warrant additional study. Experimental trials should consider clinical effectiveness, safety and side effects profiles, and feasibility of community-based treatment. Abstract : Oral and intramuscular antibiotics may provide early postpartum endometritis treatment alternatives in low-resource community settings where intravenous antibiotics are unavailable.